Solution analysis for the pseudomonotone second-order cone linear complementarity problem. (1st September 2016) - Yang, W. H.; Zhang, Lei-Hong; Shen, Chungen
Abstract : In this paper, we are concerned with the set of the solutions and the geometric property of the pseudomonotone second-order cone linear complementarity problems (SOCLCP). Based on Tao's recent work [Tao, J. Optim. Theory Appl., 159, 41–56 (2013)] on pseudomonotone LCP on Euclidean Jordan algebras, we characterize the set of solutions and also derive intrinsic properties that reveal the underlying geometry of the pseudomonotone SOCLCP.